Postponement of Pregnancy through Implant Contraceptives in View of the Theory of Maslahah Mursalah (Case Study in Bubon Sub-district, West Aceh District): Penundaan Kehamilan Melalui Alat Kontrasepsi Jenis Implan Ditinjau Dari Teori Maslahah Mursalah (Studi Kasus di Kecamatan Bubon, Kabupaten Aceh Barat) - Khairani, Khairani; Sholihin, Riadhus; Faizah, Ade (El-Hadhanah : Indonesian Journal Of Family Law And Islamic Law, 2021)
Family planning (KB) among Muslims reap the pros and cons regarding its legal status. Family planning is synonymous with limiting the number of children. Actually, family planning is not limited to this definition, but includes family planning, including one of which is delaying pregnancy by using an implant type of contraception. The formulation of the problem from this research is what factors influence the people of Bubon District, West Aceh Regency, who are less interested in implanted contraceptives and how to use implants in terms of Maslahah Mursalah's theory. This research is a field research. Types and sources of data, namely primary data and secondary data. This research was conducted using a juridical sociological approach. The data collected was studied through descriptive analysis method. The results of the research analysis indicate that the factors that influence the people of Bubon District, West Aceh Regency, are less interested in implanted contraceptives because of lack of knowledge, lack of social support, and age. Delaying pregnancy using implant-type contraceptives contains benefits or goodness. According to Islamic law, postponing pregnancy using contraception is permissible, meaning delaying pregnancy which means preventing pregnancy temporarily to give space to previous births. Whereas limiting pregnancy has the meaning of preventing pregnancy forever after having a certain number of children, it is not allowed.